Interspecific differences in growth, digestion, and feeding metabolism among freshwater fishes with different food habits - Pang, Xu; Yang, Jie; Xiang, Shen-Ao; Sun, Hao; Fu, Shi-Jian (Frontiers in Marine Science, 2024)
Studies of interspecific differences in the physiological performance of animals and their relationship with metabolism may provide insight into how selection influences diversity in phenotypic traits. To investigate the effects of food habits on growth, digestion, specific dynamic action (SDA), and the intestinal microbiota and verify their relationships in freshwater fishes, we measured the specific growth rate (SGR), meal remaining in the gastrointestinal tract, postprandial metabolic response, and intestinal microbial diversity of nine freshwater fish species with different food habits (three carnivorous, four omnivorous, and two herbivorous) fed at 25°C. The SGR, energy ingested (EI), energy efficiency (EE), gastrointestinal evacuation rate (GER), peak metabolic rate (PMR), peak metabolic scope (PMS), and SDA duration values were the highest in carnivores and the lowest in herbivores. The routine metabolic rate (RMR) and SDA coefficient values of carnivores were also significantly greater than those of omnivores and herbivores. The SGR was also significantly and positively correlated with the EI, GER, PMS, and SDA coefficients. These results indicated that growth performance, feeding and digestion abilities, and feeding metabolic responses were the strongest in carnivores and the weakest in herbivores. There was no significant difference in the richness of the intestinal microbiota with different food habits, whereas omnivores presented the highest diversity, followed by herbivores, and carnivores presented the lowest diversity. Moreover, while the phylum composition of the intestinal microbiota in fish with different food habits was similar, significant differences were observed in the composition proportions among carnivores. This might be related to the host’s ability to digest and utilize proteins, fats, and carbohydrates. We suggest that the interspecific differences in growth associated with different food habits are related to their feeding and digestive abilities, metabolic response, and gut microbiota.